Implementation of Prototyping in AI-Based Job Portal Development to Improve User Experience - Evelin Salsabila Aflahah; Hafida Zahra Sofiya Lathifa; Mochamad Rico Andreano; Prasasti Karunia Farista Ananto (Politeknik Siber Cerdika Internasional, 2026)
The rapid development of digital technology has significantly changed the recruitment system, particularly through the emergence of AI-based job portals. However, many systems still fail to meet user expectations due to a lack of user involvement early on in the development process. This study aims to analyze the implementation of prototyping in the development of AI-based job portals to improve user experience and system effectiveness. This research adopts a design-based research approach, using user needs analysis, prototype development, and iterative evaluation. Prototyping is carried out through several stages, including low-fidelity and high-fidelity models, to ensure the usability and functionality of the system. The findings show that prototyping allows for early validation, reduces development risk, and improves user satisfaction through continuous feedback integration. Additionally, artificial intelligence integration supports personalization and improves job matching accuracy. The study concludes that prototyping plays an important role in developing a user-centric digital platform and significantly contributes to improving the quality of the system and user experience. Further research is recommended to explore AI-based prototyping for more adaptive and intelligent system design.